An Experimental Study on the Axial Compressive Behavior of Normal Concrete Composite Square Columns with UHPC Internal Cores - Nguyen, Thanh Vy; Nguyen, Tuan Anh; Le, An Hoang (Engineering, Technology & Applied Science Research, 2025)
The paper presents the results of experimental tests on Normal Strength Concrete (NSC) composite square columns with Ultra-High-Performance Concrete (UHPC) internal cores of four types with a total of 24 specimens, examining the shape, number of cores, and steel fiber content to create a promising model for studying the axial compressive behavior of UHPC-NSC composite square columns. This study examines UHPC concrete with a steel fiber content of 0, 1, and 2% by volume using materials available in Vietnam in the cores. The results show that the addition of steel fibers increased the bearing capacity of the structure, while also helping to accurately evaluate the interaction between the NSC and the UHPC core. This study makes an important contribution to UHPC research in the context of limited experimental data, opening opportunities for the development of more advanced construction technologies and is of practical significance for the construction industry.